COMPARATIVE ANALYSIS OF FUNCTIONALLY-ADEQUATE CAPTURES OF MANIPULATORS OF LOADING OF SEWING MACHINES BY TEXTILE CUTTING DETAILS - Орловський, Броніслав; Місяць, Михайло (Technologies and Engineering, 2022)
Purpose. Development of a method for parametric comparative analysis of functionally adequate grips of manipulators for loading sewing machines with textile cut details. Methodology.The method of correlation-regression analysis and expert assessments are applied, which allow to quantitatively substantiate the adoption of rational decisions at the design stage when developing a technical proposal. Statistical analysis avoids the strict requirements imposed on the system of experts’ advantages in the directed vector method, which is analogous to the statistical model and has a number of advantages over the well-known method of a priori ranking of factors. Findings. For a comparative analysis of functionally adequate grips of textile parts cut modules of sewing manipulators, a generalized indicator of the quality of the process of piece-by-piece separation of parts from a pack is proposed, depending on several parameters. The successive elimination of non-essential parameters and the restructuring of mathematical models have simplified the models, in which the most important parameters are left for the development of manipulator grip modules for robotic sewing and sewing machine automation. Originality. The main regularities are revealed and mathematical models are constructed for the proposed generalized indicator of the quality of the process of piece-by-piece separation of cut parts from textiles from a pack, depending on several parameters. Practical value. A method has been developed for a parametric comparative analysis of functionally adequate manipulator grips for automatic loading of general-purpose sewing machines with textile cut parts.